Achievement Motivation and Prosocial Behavior as Predictors of Social Loafing among University Students in Lampung - Iin Yulianti; Alsya Syarifatul Hidayah; Zaizul Ab Rahman (Universitas Islam Negeri Raden Intan Lampung, 2025)
Group based activities are common in university settings, both for completing academic assignments and for participating in organizational activities. While group work can provide various benefits, it may also produce negative effects, such as the tendency of some students to reduce their effort when working collectively, a phenomenon known as social loafing. This study aims to examine whether achievement motivation and prosocial behavior influence social loafing among active university students in Lampung. The population of this study consisted of 350 active university students in Lampung, who were recruited using a purposive sampling technique. Three psychological scales were used in this research: the social loafing scale (α = 0.965), the achievement motivation scale (α = 0.828), and the prosocial behavior scale (α = 0.863). The data were analyzed using correlation analysis with the assistance of JASP software version 0.16.4. The results indicate a significant relationship between achievement motivation, prosocial behavior, and social loafing (R = 0.453, F = 44.912, p < .001). Based on the r-square value (coefficient of determination), the model explains 20.6% of the variance in social loafing, indicating that achievement motivation and prosocial behavior jointly contribute to predicting social loafing. The remaining 79.4% may be explained by other variables not examined in this study. Keywords: achievement motivation, prosocial behavior, social loafing, university students